THE EFFECT OF DIFFERENT TEMPERATURE TOWARD THE SURVIVAL RATE AND SPECIFIC GROWTH RATE OF THE SILVER ARWANA FISH (Osteoglossum bicirrhosum) - Eric Armando; Maheno Sri Widodo (Universitas Tidar, 2018)
The business of arwana hatchery is now grew up. One of the main factors which can increase the successfulness of arwana hatchery is water quality parameter, such temperature. This research was held on February to April 2014 in BBI Punten, Batu. The silver arwana hatchery was from “MINA KARYA KOI CENTER” Sleman witch its height 5,3 cm and weight 0,5 gr. It was treated in the aquarium 100x40x50 cm3 with its density 10 fry/aquarium. The treatment which given such (A) the temperature is 26oC, (B) the temperature is 28oC, and (C) the temperature is 30oC in 5 time repeated. The silver arwana hatchery which treated in thetemperature 26oC has the survival rate as 78% and the lowest score for temperature 30oC treatment is 20%. In 26oC temperature, the average of height growth is -2,7 cm and the average of weight growth in a day is 2,05%.